CONTEXTUALIZAÇÃO E AS PERSPECTIVAS DA EDUCAÇÃO SALESIANA A PARTIR DO DOCUMENTO DAS LINHAS ORIENTADORAS DA MISSÃO EDUCATIVA DO INSTITUTO DAS FILHAS DE MARIA AUXILIADORA - SOARES, SILVANA (2015)
This work aimed to contextualize and analyze the prospects of Salesian education from the document Lines Guiding the educational mission of the Institute of the FMA in order to deepen the historical and socio-cultural context of the foundation of the Institute of the FMA and development of the Salesian educational mission, in order to act in the field of education, indicate the interdisciplinary fundamentals, including the theoretical foundations for the educational practice with the sociological aspects, anthropological, theological and educational, as well as some practical experiences of education Salesian. The research considers the context of its educational practices from various theoretical contributions made about the history of the Institute and interdisciplinary skills that integrate its purpose and its educational projects. With a view to considering the document guidelines and content is used documentary analysis technique to interpret its meaning, analyze and indicate some prospects for Salesian education present in the document and involving its principles, aims and their actions regarding the education. Through participant observation some practical aspects of the prospects of Salesian education were demonstrated. Therefore, the research allows the mapping of key prospects salesina education from the Guidelines and the possibility of deepening the significance of the reference outlook for the educational practice as are indicated in the document: the cultural, evangelising, social and communicative dimensions of education which are the key elements and principles of the Education System Salesian. The design of Salesian education that is built upon an interdisciplinary, complex and dimensional vision, with a perspective of a projectual strategy. Its principles are part of some values that are considered fundamental for the realization of a comprehensive education: the educational community, the educational work in teams, youth spirituality, preventividade and environmental pedagogy. Above all, the central points indicated by the document guide communities to the realization of a projectual thought, considering the various dimensions of education, with a special opening for continuous projection of their intentions and their educational practice. Finally, we find some contributions to education from the pedagogical and practical thinking of Salesian education, especially in relation to the proposal of thinking about education complex and multidimensional way.